Exploring use of activity monitors for patients with obesity during weight-loss treatment - a qualitative study - Ingrid S. Følling; Line M. Oldervoll; Christina Hilmarsen; Ellen M. I. Ersfjord (BMC, 2021)
Abstract Background Obesity is a major health concern in western countries. In Norway, patients with obesity can attend weight-loss programmes, which focus on changes in dietary and physical activity habits. Use of self-monitoring is advocated when changing dietary and physical activity habits for adults with obesity. This study aimed to explore the experiences of patients with obesity who used activity monitors while attending a weight-loss programme. Methods Patients with body mass index (BMI) > 35 kg/m2 with weight related comorbidities or a BMI > 40 kg/m2 referred to an intermittent weight-loss programme were recruited into this study. They were introduced to one of three different activity monitors, Fitbit Zip™, Mio Fuse™, or Mio Slice™. Semi-structured interviews were performed with patients six months into the weight-loss programme. Thematic analysis was applied when analysing the data. Results Of the 29 informants (aged 21 to 66 years) interviewed, 59% were female. Their experience with activity monitors was related to their adherence to the weight-loss programme. Two main themes emerged from the informants stories: 1. "Activity monitors visualize proof of effort or failure to change health habits". 2. "Activity monitors act as a positive or negative enforcer when incorporating change". Conclusions Using activity monitors either strengthens or undermines patients' attempts to change health habits when attending a weight-loss program. Our findings suggest a need for more individualized weight-loss programmes for patients with obesity.